2016
DOI: 10.1111/sms.12744
|View full text |Cite
|
Sign up to set email alerts
|

Ice slurry ingestion does not enhance self‐paced intermittent exercise in the heat

Abstract: Insect pollination underpins apple production but the extent to which different pollinator guilds supply this service, particularly across different apple varieties, is unknown. Such information is essential if appropriate orchard management practices are to be targeted and proportional to the potential benefits pollinator species may provide. Here we use a novel combination of pollinator effectiveness assays (floral visit effectiveness), orchard field surveys (flower visitation rate) and pollinator dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…During intermittent sprint exercise in the heat for example, ice slurry consumption reduced core temperature (start of protocol -0.5°C, end of protocol -0.3°C) and thermal sensation (-3) but did not influence the total distance covered or speed during jog, run and sprint phases of the protocol (Gerrett et al 2017). As skin temperature and RPE were not different, the authors concluded, in congruence with previous work (Duffield and Marino, 2007), that combined alterations in core and skin temperature are necessary for influencing intermittent sprint performance in the heat (Gerrett et al 2017). The CISP has been utilised in experiments where various manipulations of temperature perception and actual temperature have occurred.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…During intermittent sprint exercise in the heat for example, ice slurry consumption reduced core temperature (start of protocol -0.5°C, end of protocol -0.3°C) and thermal sensation (-3) but did not influence the total distance covered or speed during jog, run and sprint phases of the protocol (Gerrett et al 2017). As skin temperature and RPE were not different, the authors concluded, in congruence with previous work (Duffield and Marino, 2007), that combined alterations in core and skin temperature are necessary for influencing intermittent sprint performance in the heat (Gerrett et al 2017). The CISP has been utilised in experiments where various manipulations of temperature perception and actual temperature have occurred.…”
Section: Discussionmentioning
confidence: 95%
“…This approach is such that it may facilitate different responses due to the elevation in pacing associated with these tasks, differentiating it from the CISP which implements fixed duration and fixed frequency of sprinting. In light of alterations in both low and high intensity running with heat stress (Konefal et al 2014;Nassis et al 2015;Watanabe et al 2017), changes in these movement velocities could also be quantified using this approach in a similar manner to other work (Gerrett et al 2017). Finally, the CISP is only 40 min in duration and therefore only replicates the first half of a field-based team sport.…”
Section: Experimental Considerations and Future Directionsmentioning
confidence: 99%
“…Regarding sport modality, studies included a wide variety of athletes, both individual (cyclists [18,19,24,30,[37][38][39][40][41][42], runners [20][21][22]43], triathletes [23][24][25]42], and tennis players [26]), and team-sport players (covering cricket [27][28][29], soccer [31], lacrosse [32], and other non-specified team sports [33]). Furthermore, three studies included volunteers who recreationally practice various sport activities [34][35][36]. Table 1 summarizes the main results of the selected studies.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…All the studies analyzed the acute effects of pre-cooling on sports performance and compared it with non-pre-cooling controls. A total of 20 studies evaluated external techniques through 28 interventions [18][19][20][21][22][24][25][26][27][28][29][31][32][33][37][38][39][40][41]43], 8 assessed internal techniques (intake of ice or cold water) [23,30,31,[34][35][36]42,43], and 3 investigated mixed strategies (a combination of external and internal methods) [31,40,43].…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…When it comes to the measurement of elite endurance performance, a time trial off ers direct assessment and time to exhaustion as well provides reliable prediction of endurance capacity (Amann, Hopkins, & Marcora, 2008). Gerrett et al (2017) measured eff ect of ice slurry ingestion on self-paced intermittent exercise, the test of which was originally designed for soccer-specifi c intermittent movements primarily taxing the anaerobic capacity. Th is study clearly did not assess the specifi c construct of endurance capacity for the purpose of their meta-analysis.…”
Section: Methodsmentioning
confidence: 99%